THE BUILDING PROJECT FOR CAR TRESTLE AS A PART OF THE TERMINAL COMPLEX AT INTERNATIONAL AIRPORT “BORISPOL” - Zorkin, Yu. S.; Lozitskiy, V. M. (Science and Transport Progress, 2010)
In the article it is presented the basic content of construction project for car trestle as a part of the terminal complex at international airport «Borispol» worked out by the State Enterprise «The research and design institute of transport construction «Kievgiprotrans» in accordance with the specifications approved by the Representative Office of «Догуш Иншаат Ве Тиджарет Аноним Ширкети» and with the project estimate documentation.